Brazil - Raising the Quality of Public Spending and Resource Management in the Health Sector - Couttolenc, Bernard; La Forgia, Gerard; Matsuda, Yasuhiko (World Bank, Washington, DC, 2012)
The report assesses how the processes of allocation, transfer, and utilization of resources are conducted at the different levels of the system. The study provides valuable information regarding the reality of the executing units of the system and how these relate to the central levels. It also seeks to identify problems related to financial flows, analyze how resources are used at the local level, and estimate their impact on the efficiency and quality of health services in general. In this respect, the study provides a basis for improving the entire cycle of public resource management processes (i.e., planning, budgeting, budget execution, input management, and health service production) in the health sector, which together help to bolster good governance in health care delivery. This report referenced in this note assesses resource allocation and management, planning and budgeting functions, and budget execution at different levels of government for public expenditures on health services. The emphasis is on understanding the incentives generated for service providers, and the overall soundness of the accountabilities established in the public health services expenditure system. The analysis seeks to identify weaknesses of accountabilities for service provision that stem from the structure and process of intergovernmental and provider funding flows and related managerial practices.